(untitled) (Future Cities and Environment, 2024)
This study explores various factors that influence the consumer’s intention to adopt smart, green, and sustainable building materials in Bangalore city, Karnataka, India. The purpose of this study is to evaluate how consumers’ actual adoption behaviour of smart, green, and sustainable building materials is influenced by their behavioural intentions. A standardized questionnaire was utilized to collect data from 382 homebuilders in Bangalore as part of a descriptive research study. A simple random sampling technique was used along with Structural equation modelling (SEM) was employed to test hypotheses framed. Findings indicate that availability and accessibility, awareness, epistemic values, and technology adoption propensity all positively affect subjective norms. Subjective norms positively impact behavioural intention and adoption behaviour. However, challenges in adoption influenced subjective norms negatively, thus hindering consumer adoption. Awareness had the greatest influence on subjective norms, emphasizing the need for increasing consumer awareness. Subjective norms successfully mediated the relationship between independent factors impacting behavioural intention and adoption behaviour. Significant indirect effects of awareness via subjective norms on Behavioural intention were observed. This study highlights the need of increasing social awareness and cultivating a positive view of social expectations in order to promote the widespread use of smart, green, and sustainable building materials, which will eventually result in long-term sustainable cities and surroundings.